ABNORMAL ANALYSIS OF RETURN AND TRADING VOLUME ACTIVITY DURING THE COVID-19 PANDEMIC - Peny Prastiwi Rahayu; Wahidahwati (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2024)
This study aims to determine investor reactions from announcements given by the Government of Indonesia regarding the COVID-19 pandemic. In this study, investors' reactions were seen from whether there were abnormal differences in return and trading volume activity before and after the announcement. The announcements used in this study were the announcement of the first COVID-19 patient in Indonesia, the announcement of the PSBB and the announcement of the new normal. The sample used was 45 shares of companies listed in LQ45 on the IDX. The window period used in this study is 15 days, which is 7 days before the announcement, 1 day of announcement and 7 days after the announcement. The data analysis technique used is the paired sample t-test. The test results of this study show that there is investor reaction, judging from the abnormal return around the announcement of the first COVID-19 patient in Indonesia, the announcement of the PSBB and the announcement of the new normal.  Hypothesis testing shows that there are abnormal differences in return and trading volume activity before and after the announcement of the new normal. Meanwhile, there were different results in abnormal return testing and trading volume activity before and after the announcement of the first COVID-19 patient and the announcement of the PSBB, which showed no significant difference.